The Link between Globalisation, Economic Growth and Education: An Analysis in the Case of Romania - Dima, Stela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The paper tries to offer empirical evidence on the link between economic growth, globalisation phenomenon and education level of population in the Romanian economy. Using time series for 1990-2011 in a regression model, we found a positive validated correlation between globalisation and economic growth, globalisation and education and, economic growth and education. For globalisation measurement the KOF index of globalisation was used.